Does a dynamic chair increase office workers' movements? – Results from a combined laboratory and field study. (April 2017) - Grooten, Wilhelmus J.A.; Äng, Björn O.; Hagströmer, Maria; Conradsson, David; Nero, Håkan; Franzén, Erika
Abstract: Purpose: Dynamic chairs have the potential to facilitate movements that could counteract health problems associated with sedentary office work. This study aimed to evaluate whether a dynamic chair can increase movements during desk-based office work. Methods: Fifteen healthy subjects performed desk-based office work using a dynamic office chair and compared to three other conditions in a movement laboratory. In a field study, the dynamic office chair was studied during three working days using accelerometry. Results: Equivocal results showed that the dynamic chair increased upper body and chair movements as compared to the conventional chair, but lesser movements were found compared to standing. No differences were found between the conditions in the field study. Conclusions: A dynamic chair may facilitate movements in static desk-based office tasks, but the results were not consistent for all outcome measures. Validation of measuring protocols for assessing movements during desk-based office work is warranted. Highlights: Dynamic chairs may facilitate movements compared to conventional chairs. The performed task have a greater impact on movements than chair-condition. New protocols for measuring movements in desk-based office work are warranted.